Histomorphometric analysis of the endothelial cell in skin microvasculature among diabetic foot ulcer patients - Mohd Radzuan, Hazulin; Myint, Yi Yi; Tun, Ye; Zulkifly, Ahmad Hafiz (2011)
Changes affecting endothelial cells in the microcirculation of diabetic foot patients are important in the development of foot ulceration and subsequent failure to heal existing ulcers.